Preparation of Paclitaxel-Loaded Alginate-Chitosan Complex Microcapsules (Journal of Fiber Bioengineering and Informatics, 2014)
Paclitaxel-loaded alginate-chitosan complex microcapsules were successfully prepared by the high-voltageelectrostatic technique. The effect of paclitaxel concentration and drug-loading methods on drug loadingof alginate-chitosan microcapsules, and the effect of methanol concentration, chitosan concentration andchitosan molecular weight on encapsulation efficiency were investigated. Experimental results showedthat calcium alginate beads had a good degree of sphericity and a uniform size of 299.8 ± 3.6  μm. Afterencapsulation with chitosan membrane followed by freeze drying, microcapsules shrunk and collapsedwith a mean particle size of about 60.0 μm. Drug loading results showed that as paclitaxel concentrationincreased from 2 mg/mL to 8 mg/mL, drug loading of microcapsules was increased from 1.95% to 11.16%.Microcapsules with dynamical paclitaxel-loading at 30 °C had the highest drug loading, followed bythose with statical paclitaxel-loading at 4 °C and 37 °C. Encapsulation efficiency results showed thatmicrocapsules washed with 0.5% (v/v) methanol had the highest encapsulation efficiency of 2.85%.The encapsulation efficiency was decreased with the increase of chitosan concentration, while it firstlydecreased and then increased with the increase of molecular weight of chitosan. These results provideprimary information about drug loading and encapsulation efficiency properties of paclitaxel-loadedalginate-chitosan microcapsules as a novel drug carrier.
Keywords: Paclitaxel; Alginate; Chitosan; Microcapsules; High-voltage Electrostatic Technique